Elementy włoskości w polskim nazewnictwie miejskim i wiejskich mikrosystemach toponimicznych - Ozimska, Joanna (Doświadczanie i wyrażanie włoskości: Aspekty językoznawcze i glottodydaktyczne, 2021)
The study focuses on street names in Polish cities, towns and villages, in particular it examines Italian references within contemporary Polish odonymy. The author has performed a semantic and structural analysis of 554 units, applying the classification proposed by K. Handke. The results from the study of name usage show that there are 0,20% of proper names referring to Italianness on Polish streets, and 2% of them are motivated. Most names derive from other proper names. The most common are street names taking origin from anthroponyms (44%) – commemorate figures that are deemed to be important to the local community (saints, artists, musicians, patriots, explorers). They are followed by names derived from place names (20% – cities, 11% – other toponyms). 7% of corpus are names derived from ethnonyms. On the other hand, there are street names not subject to the transonimisation process and they represent 12% of corpus. The paper also provides a list of the most frequent street names and information about geographical differentiation of urban and rural street names, as well as a short presentation of female street namesakes.